Happiness from the teaching experience: mental health well-being during the COVID-19 pandemic - Chavez Taipe, Ysabel Victoria; Ayvar Bazán, Zoila; Huaita Acha, Delsi Mariela; Cornejo Guevara, Maria Elena; Lozano Lozano, Marilé; Albarrán Gil, Jorge Luis (Horizonte Sanitario, 2025)
Objective: To determine perceptions of happiness from teaching experiences during the COVID-19 pandemic at the end of the 2021 academic year. Materials and Methods: The methodology used is applied, with a population of 457 education professionals from public elementary schools in the Institutional Education Network (REI) in Lima, Peru, and a non-probabilistic sample of 104 teachers. The data collection tools used the happiness scale to measure the positive meaning of life. Results: 51% reported a high level of happiness. Regarding the dimension “positive meaning of life,” the majority (76%) reported a high level. In addition, 59.6% reported a moderate level of “personal fulfillment,” and 82.7% of participants reported a high level of “joy of living.” Conclusions: Happiness, a life project based on teaching experiences, during the pandemic can be described as a way to increase the impact of positive feelings and was proposed favorably in terms of happiness levels despite the influential situations of COVID-19. Keywords: Experience; Mental Health; Pandemic COVID-19.